Peningkatan Kemampuan Pemahaman Konsep Himpunan Melalui Pembelajaran Matematika dengan Media Articulate Studio’13 - Farida Farida; Suherman Suherman; Sofwan Zulfikar (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
The purpose of this study was to produce media products based on articulate Studio'13 in mathematics subjects that were appropriate, interesting and effective in learning. This research is a type of research and development (R & D) by modifying 10 stages into 7 stages, namely; potential and problems, information collection, product design, design validation, design revisions, product trials, and product revisions. Assessment of media feasibility is carried out by material experts and media experts. Assessment and attractiveness of students. The effectiveness of the product is seen as a percentage > 75% of the number of students who passed the KKM. This research resulted in Articulate Studio '13 learning media proven to be valid and feasible to be used as learning media after getting a score of 88.3% from 3 material experts, and a value of 86.1% from 3 media experts. For attractiveness assessments get the criteria